Surgical lung biopsy for the diagnosis of interstitial lung disease: a review of the literature and recommendations for optimizing safety and efficacy - Nguyen, W.; Meyer, K.C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Making an accurate diagnosis of a specific type of interstitial lung disease (ILD) requires a structured and comprehensive approach that includes a complete patient history, careful physical examination, appropriate laboratory testing, and thoracic imaging. If invasive procedures are required, bronchoscopy with bronchoalveolar lavage (BAL) and/or endoscopic lung biopsy (ELB) can frequently establish a confident diagnosis. However, surgical lung biopsy (SLB) may be required to make a confident diagnosis. Because SLB may be associated with a significant risk of morbidity and mortality, we performed a comprehensive literature review of all available literature published in the English language that reported outcomes of surgical lung biopsy performed for the diagnosis of ILD. The overall 30-day mortality for open lung biopsy (OLB) was 4.3% versus 2.1% for video-assisted thorascopic surgery (VATS) biopsy, and non-lethal complications appeared to occur more frequently with OLB (18.1%) vs. VATS (9.6%) procedures. In addition to presenting the results of our comprehensive literature review on SLB for the diagnosis of ILD, we suggest an approach that minimizes risks to patients and optimizes the diagnostic utility of SLB when SLB must be performed to obtain a confident ILD diagnosis.